2009
DOI: 10.1111/j.1365-2885.2009.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic evaluation of propofol administered to cats in a novel, aqueous, nano‐droplet formulation or as an oil‐in‐water macroemulsion1

Abstract: This study evaluated pharmacokinetic and pharmacologic properties of a novel, non-lipid microemulsion, 1% w/v formulation of propofol to a conventional macroemulsion formulation of propofol (Rapinovet) in cats. The study utilized a two-period crossover design with two treatments and 10 female, intact, purpose bred domestic shorthair cats. Cats were fitted with telemetry transmitters for direct measurement of arterial blood pressure, pulse rate, electrocardiogram (ECG, lead II), and body temperature. At least 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…The clearance of propofol in cats undergoing ketofol infusion was quite slow (692.36 ± 326.18 mL/h/kg) and lower than that reported in cats after single IV bolus (Cl B 1032 mL/h/kg; Cleale et al. , 2009) and in other species after propofol and ketamine infusion (Nolan & Reid, 1993; Correia et al.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The clearance of propofol in cats undergoing ketofol infusion was quite slow (692.36 ± 326.18 mL/h/kg) and lower than that reported in cats after single IV bolus (Cl B 1032 mL/h/kg; Cleale et al. , 2009) and in other species after propofol and ketamine infusion (Nolan & Reid, 1993; Correia et al.…”
Section: Discussionmentioning
confidence: 62%
“…However, the sampling time in our study and the reported studies in sheep and dogs was 24 h after the end of the infusion, whereas the infusion time was shorter in cats than in the other mentioned species (<30 min vs. 60 min). After a single IV bolus of propofol in cats, an elimination half‐life of 8.7 h was reported (Cleale et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre grupos, a PaCO 2 do EMU foi maior de T15 até T90 em relação ao MICRO. A diferença apresentada pode ser atribuída à formulação do propofol em microemulsão, frente ao metabolismo diferenciado dos gatos, uma vez que esse episódio não ocorreu em estudo de CORRÊA et al (2010), utilizando a mesma formulação em cães, bem como em outros estudos, utilizando diferentes formulações de propofol em cães (MOREY et al, 2006) e gatos (CLEALE et al, 2009).…”
Section: Resultsunclassified